Impact of pomegranate peel as prebiotic in bio-yoghurt. Issue 9 (21st May 2020) - Ibrahim, Amel; Awad, Sameh; El-Sayed, Mahmoud
Abstract : Purpose: The effect of pomegranate whole and inside peels before and after extraction of the tannic acid have been carried out in stimulated media and in gastrointestinal conditions Design/methodology/approach: Adding pomegranate peels with and without tannins at different levels to bio-stirred yoghurt to study its effect as prebiotic, in addition to evaluating the effect on physiochemical, sensorial and rheological properties Findings: The results reveal that pomegranate peels before and after removing tannins had no effect on the viability of a single strain of Lb. acidophilus in stimulated media, while the growth of mixed probiotic culture (Lb.acidophilus and Bifidobacterium bifidum ) was enhanced when pomegranate peels (whole and inside part) free from tannins were used. Tannin-free pomegranate peels enhanced the viability of probiotic culture under gastrointestinal conditions. In this study, all probiotic cultures were maintained counts around log 8 cfu /g in stirred bio-yoghurt supplements with pomegranate peels after 21days. Bio-yoghurt supplemented with pomegranate peels at 0.5% gained high scores for overall acceptability. Originality/value: Pomegranate has been recognized as a good source of antioxidant and antimicrobial activities. Some researchers have utilized pomegranate peel in fermented milk, but most of the studies have found that tannins inhibit the bacterial culture. This study recommended that the supplementation of low-fat bio-yoghurt with tannin-free pomegranate peels enhanced the texture properties, viscosity of the product, as well as the viability of probiotic culture during shelf life. Therefore, the tannin-free pomegranate peel could be used as a prebiotic in functional fermented dairy products.